The master regulator MAT1-1-1 of fungal mating binds to its targets via a conserved motif in the human pathogen Aspergillus fumigatus - Ramsak, Barbara; Markau, Jessica; Pazen, Tobias; Dahlmann, Tim A.; Krappmann, Sven; Kück, Ulrich (G3 : Genes, Genomes, Genetics, 2021)
Mating-type transcription factors are master regulators of sexually related signal transduction pathways in fungi; however, their recognition of specific DNA sequences from target genes is widely undetermined. Here, we identified and characterized the DNA-binding sequence of the MAT1-1-1 alpha-box domain transcription factor from the human pathogen Aspergillus fumigatus. In order to explore MAT1-1-1 DNA-binding targets, we used the previously reported MAT1-1-1 binding motif from Penicillium chrysogenum, in a bioinformatics approach. We identified 18 A. fumigatus genes carrying the MAT1.1 sequence in their upstream region, among them genes for the a-pheromone precursor (PpgA), G-protein-coupled pheromone receptor (PreA), and for TomA, an unidentified protein. To validate our prediction further, quantification of transcript levels showed a decrease in expression of ppgA, tomA, and others in a MAT1-1 deletion strain. For a functional analysis of the binding sites, truncated variants of the A. fumigatus MAT1-1-1 gene were introduced into Escherichia coli for heterologous expression. The yield of recombinant protein was further optimized for the AfMAT1-1-178–235 variant that harbors an extended alpha-box domain. AfMAT1-1-178–235 bound to a subset of the most strongly upregulated genes: ppgA, preA, and tomA. The DNA-binding specificity was confirmed by testing mutated binding sequences, as well as performing competition experiments with specific and non-specific sequences. Finally, equilibrium dissociation constants of 1.83 6 0.1 and 1.45 6 0.26 mM were determined for AfMAT1-1-178–235 and fusion protein GST-AfMAT1-1-178–235. Collectively, these findings provide further insights into AfMAT1-1-1-mediated gene expression and imply that alpha-box domain regulators from other members of Eurotiales control fungal development in a conserved manner.
CRIS-Team Scopus Importer:2021-03-26
Keywords: DNA-binding motif; Escherichia coli protein synthesis; Human pathogen Aspergillus fumigatus; Mating type; Transcription factor